Istiḥsān Theory and Its Application in the Standard Inpatient Class (KRIS) Initiative by the National Health Insurance Program (JKN) - Afthon Yazid; Siti Aminah; Dwi Karina Ariadni; Thoha Yasin Utsman; Arif Sugitanata (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2024)
This research aims to discuss the Standard Inpatient Class (KRIS) initiative which is integrated into the National Health Insurance Program (JKN) in Indonesia. This program was implemented to improve the quality and access of health services. KRIS is designed to improve the physical aspects of health facilities, but challenges arise in its implementation, including adapting hospital infrastructure and varying public perceptions. This research uses a qualitative method with a literature review approach, namely by collecting various sources relevant to the research topic. Data sources include scientific articles, books, research reports, government regulations, and other official documents related to the implementation of KRIS by JKN and analyzed using istihsan theory. The results of the research are that although hospitals in Indonesia are generally ready to implement KRIS, BPJS Health still considers its implementation to be no longer relevant due to a budget surplus. On the other hand, if viewed using the istiḥsān theory, the KRIS program initiative is the implementation of government steps to achieve social justice and equal access to health services. This article also highlights differences of opinion between BPJS Health and the National Social Security Council (DJSN) as well as the lack of clarity in existing law regarding the government's role in implementing KRIS. This research shows the need for adjustments and better communication between stakeholders to ensure the success of KRIS in achieving the goals of the National Health Insurance Program (JKN-KIS).